Molecular Structure, Spectroscopic, Frontier Molecular Orbital Analysis, Molecular Docking Studies, and In Vitro DNA-Binding Studies of Osmium(II)-Cymene Complexes with Aryl Phosphine and Aryl Phosphonium Assemblies - Kgaugelo C. Tapala; Nqobile G. Ndlangamandla; Mpho P. Ngoepe; Hadley S. Clayton (Bioinorganic Chemistry and Applications)
X-ray crystallography, spectroscopy, computational methods, molecular docking studies, and in vitro DNA-binding studies have been useful in the investigations of intermolecular and intramolecular interactions of osmium-cymene oxalato complexes with aryl phosphine and aryl phosphonium groups in both primary and secondary coordination spheres, respectively. Molecular structures of the novel complexes PPh4[Os(η6-p-cymene)Br(κ2-O,O′-C2O4)] (1) and [Os(η6-p-cymene) (κ2-O,O′-C2O4)PPh3] (2) were resolved by single-crystal X-ray diffraction (XRD). Primary and secondary coordination sphere contacts were investigated using Hirshfeld surface analysis which was supported by molecular docking (MD) studies. The MD data obtained predicted significant differences in binding energy across three receptors for the two osmium complexes. An in vitro DNA-binding study was accomplished using UV-Vis spectroscopy which showed that both 1 and 2 bond with DNA through an intercalation approach. The optimized molecular geometry, frontier molecular orbital (EHOMO and ELUMO) energies, global electrophilicity index (ω), chemical hardness (η), chemical potential (µ), and the energy band gap (EHOMO–ELUMO) were calculated utilizing density functional theory (DFT) methods. Computed structural parameters (bond lengths and angles) support the experimental single-crystal XRD data.